Emergency Cancer Care - Todd, Knox H.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Emergency Cancer Care is the first journal dedicated to the emerging subdiscipline of oncologic emergency medicine. The journal promotes new knowledge and scholarly exchange, serving as a multidisciplinary platform of communication for the many disciplines involved in caring for oncologic emergencies. Emergency Cancer Care publishes original research reports, reviews, and editorial commentary to advance science and practice in this unique subspecialty field. In addition to the evaluation and treatment of oncologic emergencies, the journal addresses cancer treatment toxicities, prevention opportunities in the emergent setting, and emergency department-based palliative care, as well as health services research and policy. Manuscripts addressing non-malignant hematology and sickle cell disease are also encouraged. .
Keywords: Medicine; Emergency medicine; Oncology; Clinical Medicine; Emergency Medicine; Oncology